GAMBARAN TENTANG SELF EFFICACY DAN RESILIENCE PADA LANSIA DI PANTI JOMPO PUCANG GADING SEMARANG - Naufal Muhammad Agil; Elis Hartati (Jurnal Ilmu Keperawatan Komunitas, 2022)
The elderly need self-efficacy when carrying out mental activities to solve daily problems. The elderly also need resilience skills to maintain the stability of the system in themselves. Self-efficacy and resilience in holistic nursing are categorized on the psychological dimension. Disruption of the psychological dimension as a system causes a domino effect on other dimensions. This results in the loss of existence and even transcendence of the elderly. Elderly with good self-efficacy and resilience have the ability to behave in an adaptive and positive manner so that they can achieve a productive and satisfying life. The description of self-efficacy and resilience provides benefits for researchers and parties around the elderly to help the elderly live their old age successfully. The purpose of this study was to identify self-efficacy and resilience in the elderly at Panti Wredha Pucang Gading Semarang. This study uses a descriptive quantitative research method. The sampling method is total sampling with a sample of 82 respondents. The results showed that the elderly had high self-efficacy as many as 50% of respondents, and 66% of respondents had low levels of resilience. The elderly can increase self-efficacy by implementing the Healthy Aging MBI program, practicing daily living (ADL) activities independently and spending time with close friends. Elderly can practice resilience skills by developing coping strategies and staying away from loneliness. The participation of all parties is expected to pay attention to the importance of self-efficacy and resilience of the elderly for a better quality of life.